(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2024)
In the struggles of social movements and feminisms, the practice of listening plays, and has played, a fundamental role in the emancipation of the voices of subaltern subjectivities and in the collective co-construction of the idea of political voice. This article aims to highlight two political and epistemological aspects that have influenced the practice of listening as it is explored today in contemporary artistic research: firstly, the overcoming of the phenomenological tradition that canonised listening as a purely perceptual, acoustic and technical phenomenon; secondly, how listening has begun to deal not only with the audible, the sonorous, the acoustic, but above all with the inaudible, with what is not audible, with what is not heard because it is invisible and/or made not visible, because it has no voice, because it is silenced, redefining listening as a mode of intergenerational and intersectional transmission of knowledge. To do this and to better understand the role of second-wave feminism in the genesis of listening as a practice, I will present here the Italian translation of some passages from Lucia Farinati and Claudia Firth’s publication The Force of Listening, a key publication on the legacy between listening and feminist practice.